Evaluation of selected solid adsorbents for passive sampling of atmospheric oil and natural gas non-methane hydrocarbons. (4th March 2022) - Helmig, Detlev; Fangmeyer, Jens; Fuchs, Joshua; Hueber, Jacques; Smith, Kate
ABSTRACT: This project investigated passive adsorbent sampling of light (C2 -C5 ) hydrocarbons which are sensitive tracers of fugitive emissions from oil and natural gas (O&NG) sources. Stronger adsorbent materials, i.e. Carboxen 1000 and Carboxen 1016, than those typically used in adsorbent sampling were considered. Experiments were conducted in laboratory and field settings using thermal desorption – gas chromatography analysis. Uptake of water vapor and system blanks were challenges inherent to the increased affinity of these adsorbents. Carboxen 1000 exhibited the best signal-to-noise ratio for the target compounds after optimizing conditioning parameters to reduce blanks, and by reducing the adsorbent mass loaded in the cartridge. This strategy reduced blanks to equivalent ambient air mole fractions of <0.05 nmol mol −1 (ppb), and allowed determination of these O&NG tracers over three-day sampling intervals with a lower detection limit of ≥0.5–1 ppb. Linear VOCs uptake was observed in dry air. Water uptake was as high as 0.65 gH2O g −1 adsorbent at relative humidity (RH) above ≈ 75%. The water collection passivates adsorbent sites and competes with the uptake rates of VOCs; under the worst case relative humidity level of 95% RH, VOCs uptake rates dropped to 27–39% of those in dry air. This effect potentially causes results to be biased low when cartridges are deployed at high relative humidity (RH), including overnight, when RH is often elevated over daytime levels. Nonetheless, representative sampling results were obtained under ambient conditions during three field studies where cartridges were evaluated alongside whole air sample collection in canisters. Agreement varied by compound: Ethane and alkenes correlated poorly and could not be analyzed with satisfactory results; results for C3 -C5 alkanes were much better: i -butane correlated with R 2 > 0.5, and propane, n -butane, i -pentane, and n -pentane with R 2 > 0.75, which demonstrates the feasibility of the passive sampling of these latter O&NG tracers. Implications: Oil and natural gas development has been associated with emissions of petroleum hydrocarbons that impact air quality and human health. This research characterizes and defines the application possibilities of solid adsorbent sampling for atmospheric passive sampling monitoring of low molecular weight volatile organic compounds (i.e. ethane through pentane isomers) that are most commonly emitted from natural gas drilling and well sites. The passive sampling of these pollutants offers a simple, low cost, and readily applicable monitoring method for assessing emissions and air quality impacts in the surroundings of oil and gas operations.